Why govern? : rethinking demand and progress in global governance - Acharya, Amitav (Cambridge : Cambridge University Press, 2016)
The system of international cooperation built after World War II around the UN is facing unprecedented challenges. Globalization has magnified the impact of security threats, human rights abuses, mass atrocities, climate change, refugee, trade and financial flows, pandemics and cyberspace traffic. No single nation, however powerful, can solve them on its own. International cooperation is necessary, yet difficult to build and sustain. Rising powers such as China, India, and Brazil seek greater leadership in international institutions, whose authority and legitimacy are also challenged by a growing number of civil society networks, private entities, and other non-state actors. Against this backdrop, what is the future of global governance? In this book, a group of the leading scholars in the field provide a detailed analysis of the challenges and opportunities facing global cooperation. The book offers a comprehensive and authoritative guide for scholars and practitioners interested in multilateralism and global order.
Machine generated contents note: 1. Rethinking demand, purpose and progress in global governance: an introduction Amitav Acharya; 2. The great descent:'global governance' in historical and theoretical perspective Daniel Deudney; 3. Who is liberal now? Rising powers and global norms Miles Kahle; 4. The social purposes of global governance Rodney Bruce Hall; 5. Conflicts and security Andrew Mack; 6. Human rights Kathryn Sikkink; 7. Atrocity crimes Ramesh Thakur; 8. Trade Susan Sell; 9. Finance Eric Helleiner; 10. Climate Sikina Jinnah; 11. Refugees Alexander Betts; 12. Health David P. Fidler; 13. Cyberspace and social media Derrick Cogburn; 14. The contested quest for global governance: conclusions and directions for further research Amitav Acharya.
Title from publisher's bibliographic system (viewed on 06 Sep 2016).
Keywords: International cooperation